Fodder crop re-allocation sustainability and risk efficiency - Kheiry Ishag (Agricultural and Food Economics, 2015)
Rhodes Grass crop is continuously cultivated in coastal area of Salalah and Batinah region of Sultanate of Oman and created a negative impact on agriculture production. The government authority stopped Rhodes grass cultivation in coastal area and encouraged farmers to develop new area at Najed. New irrigation water policy regulations imposed to reduce risk of underground water deficit and insure sustainable fodder production. Due to uncertainty of underground water availability, investors have little data to help in making investment decisions. Under these circumstances this research aims to study performance and sustainability of Rhodes grass cultivation at new developed area. The study applied a stochastic budgeting approach to evaluate proposed incentive strategies under different level of underground water. The stochastic budgeting simulation is done by using @Risk software that allows the representation of risk and uncertainty as probability distributions. Stochastic Efficiency with Respect to a Function (SERF) performed to rank different incentive alternatives for decision makers with different degrees of risk aversion and select the risk-efficient incentive strategies. The study calculated risk premium needs to be paid to a decision maker to justify switch from present location (Salalah) to new proposed area which is equal RO 97 thousand for (Hanfeed) and RO 557 thousand for (Dawkah) location. The breakeven risk aversion coefficients were calculated under different Government supporting incentives. Under lower RAC Salalah, Hanfeet2 and Dawkah2 were the most preferred scenarios respectively, whereas under upper RAC Dawkah2 followed by Hanfeet2 and Salalah were the most preferred scenarios. The results illustrate possible conflicts between risk efficiency and sustainability. Change in water policy with raw material subsidy could improve risk efficiency and encourage investors to sustain fodder crop re-allocation activates at new area at Najed.
Keywords: 330; Stochastic efficiency with respect to a function; Risk efficient; Simulation model; Risk management strategy; Sustainability